Distinctive phenotypes in two children with novel germline RUNX1 mutations - one with myeloid malignancy and increased fetal hemoglobin. (28th September 2020) - Bagla, Shruti; Regling, Katherine A.; Wakeling, Erin N.; Gadgeel, Manisha; Buck, Steven; Zaidi, Ahmar U.; Flore, Leigh A.; Chicka, Michael; Schiffer, Charles A.; Chitlur, Meera B.; Ravindranath, Yaddanapudi
Abstract: RUNX1 associated familial platelet disorder (FPD) is a rare autosomal dominant hematologic disorder characterized by thrombocytopenia and/or altered platelet function. There is an increased propensity to develop myeloid malignancy (MM) - acute myeloid leukemia, myeloproliferative neoplasms or myelodysplastic syndrome often in association with secondary somatic variants in other genes. To date, 23 FPD-MM pediatric cases have been reported worldwide. Here, we present two new kindreds with novel RUNX1 pathogenic variants in which children are probands. The first family is a daughter/mother diad, sharing a heterozygous frameshift variant in RUNX1 gene (c.501delT p.Ser167Argfs*9). The daughter, age 13 years, presented with features resembling juvenile myelomonocytic leukemia - severe anemia, thrombocytopenia, high white cell count with blast cells, monocytosis, increased nucleated red cells and had somatic mutations with high allele burden in CUX1, PHF6, and SH2B3 genes. She also had increased fetal hemoglobin and increased LIN28B expression. The mother, who had a long history of hypoplastic anemia, had different somatic mutations- a non-coding mutation in CUX1 but none in PHF6 or SH2B3 . Her fetal hemoglobin and LIN28B expression were normal. In the second kindred, the proband, now 4 years old with thrombocytopenia alone, was investigated at 3 months of age for persistent neonatal thrombocytopenia with large platelets. Molecular testing identified a heterozygous intragenic deletion in RUNX1 encompassing exon 5. His father is known to have increased bruising for several years but is unavailable for testing. These two cases illustrate the significance of secondary mutations in the development and progression of RUNX1-FPD to MM.